Penerapan Dirrect Transfer Film (DTF) dengan Motif System Neuron Jellyfish pada Busana Evening Gown - Jenifer Theresa Lopis; Yuhri Inang Prihatina (BAJU: Journal of Fashion and Textile Design Unesa, 2023)
The Neuron Jellyfish motif has a distinctive beauty and uniqueness in the form of channel lines from the branching jellyfish nerves. The research objectives are 1) to describe the application of DTF technique and 2) to know the finished result of DTF, with Neuron Jellyfiish motif system on Evening Gown fashion. This research method uses the Double Diomond method which has 4 stages, namely: the initial stage Discover stage where it determines the direction of fashion design, making an evening party dress with Jellyfish as the source of inspiration made for young women with sexy uniqe, and funky types. The second stage, Define, is the application of a source of inspiration, then creating a motif design, sketch design, and illustration design. The third stage is Develop at this stage the researcher makes a Toal trial, then creates a one-piece outfit with silhouette I, after that applying the DTF screen printing results to the main material of the outfit, then the fourth stage Deliver is the stage of delivering the finished result of the outfit. The results showed that making Evening Gown fashion needs to look at the technique of applying motif decoration, determining the colour and silhouette to match the inspiration.